The Impact of Information Age Threats on the Minds of Youth and Their Unethical Foundations (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
Today's era has truly earned the name "the age of information revolution." This is primarily due to the speed of information transmission and the development of compact technologies. Information can either lead to the decline of individual and societal spirituality or elevate it through changes and additions. Morality lies at the core of socio-ethical life, driving socio-moral experiences. The proliferation of information is also creating problems related to spirituality and morality among young people. This necessitates the systematic establishment of information and ethical relationships. The article presents thoughts, discussions, and suggestions regarding the aforementioned problems and their solutions.